The Extent оf the Spread and Activity оf the Manifestation оf Avalanche-Talus Processes in the Karachay-Cherkess Republic - V. V. Razumov; L. M. Fedchenko; N. V. Razumova; N. D. Bogdanova; V. A. Shalnev (Наука. Инновации. Технологии)
Introduction. Avalanche-talus processes have become common mainly in the mountainous regions of the Karachay-Cherkess Republic. The article provides an assessment of the extent of the spread, activity and danger of avalanche- talus processes on the territory of the republic over 2005–2022.Materials and research methods. The key method used in this work was the analysis of various materials containing information on the activity of the manifestation of avalanche-talus processes on the territory of the Karachay-Cherkess Republic. Literary sources, reports and published data of the Center for State Monitoring of the State of the Subsoil of the Federal State Budgetary Institution «Hydrospetsgeology » over the period of 2005–2022 served the main sources of the analysis.Research results and their discussion. The authors characterize the conditions and the causes, the extent of the spread, and assess the activity and danger of avalanche-talus manifestations that occurred on the territory of the Karachay-Cherkess Republic in 2005–2022. The paper provides information on the extent of destruction and deformation of settlements and economic objects under the influence of these processes.Conclusions. Information is given on the location of avalanche-talus manifestations on the territory of the Karachay-Cherkess Republic and their characteristics, the extent of destruction and deformation caused by them. Over the period in question, more than 90 significant avalanche-talus manifestations were recorded on the territory of the republic, the volumes of which did not exceed 1000–1500 m3. The largest scale of landslide-scree activity was observed in 2006, 2007 and 2010, and a low degree of activity was observed in 2017, 2020 and 2022. The majority of active landslide-talus sites (more than 85 %) were recorded on the highways of the republic. The most significant degree of their activity was noted in the Karachay and Zelenchuk administrative districts of the republic.